Malnutrition and Left Ventricular Systolic Function in Hospitalized Elderly Patients with and without Heart Failure - Santillo, Elpidio; Migale, Monica; Fallavollita, Luca; Marini, Luciano; Postacchini, Demetrio; Balestrini, Fabrizio; Incalzi, Raffaele Antonelli (Journal of Nutritional Therapeutics, 2013)
<!– [if gte mso 9]> Normal 0 14 false false false IT X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–> Heart failure (HF) is highly prevalent among older subjects and it is associated with poor prognosis. HF frequently coexists with malnutrition. Objectives of our work were to assess nutritional status of old inpatients with and without HF and to study the association of malnutrition markers with echocardiographic parameters of left ventricular function and geometry. We enrolled 165 patients (72 men, 93 women; mean age: 80±7 years) consecutively admitted to Cardiology ward of our geriatric research hospital. For all subjects we performed clinical examination, echocardiogram and laboratory tests. Nutritional status was assessed evaluating anthropometric and laboratory markers of malnutrition (BMI ≤ 24 kg/m2 and/or serum albumin ≤ 3.2 g/dL). We found high prevalence of HF (67.3%) and malnutrition (28.5%). Mean serum albumin and mean BMI were 3.6±0.5 g/dL and 25.8±5.2 kg/m2 respectively. T-Student tests showed lower values of serum albumin in patients with HF compared with patients without HF (3.5±0.6 g/dL vs 3.7±0.4 g/dL; p:0.043). Conversely BMI values were not significantly different. We found significant association between serum albumin and ejection fraction (EF) of left ventriculum (r:0.311; p:0.001). An independent correlation between EF and serum albumin was confirmed by multivariate analysis (β:0.301; p:0.027). Our study highlights that malnutrition is common among elderly inpatients with HF. Lower albumin was associated with worse systolic left ventricular function. Efforts should be made in the research setting to better understand the pathophysiology of malnutrition in HF and to identify useful management strategies for nutritional assessment and supplementation. <!– [if gte mso 9]> <![endif]–><!– [if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Tabella normale"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi; –><!–[endif] –>